High-Performance Networking for Software DSMs - Santos, Rodrigo Weber dos; Bianchini, Ricardo; Amorim, Claudio L. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1998)
Several messaging software architectures (MSAs) have been proposed and implemented for high-performance local-area networks (LANs). Several of these MSAs have been success ful at providing low latency and high bandwidth to user-level processes that communicate via explicit message passing. In this paper we claim that these MSAs are suboptimal for page-based software distributed shared-memory systems (software DSMs), as they do not consider the specific characteristics of these systems. We support our claim by studying the communication behavior of several applications running on top of the TreadMarks system and by showing that no previously-proposed architecture is ideal for the observed behavior. Finally, we propose a novel MSA for the Myrinet LAN that is tailored to software DSMs. This new design includes isolated features from some other MSAs, offering reliable message delivery, optimizations for both short and long messages, and several options for message arrival notification. In addition, our proposed MSA relies on a communication model that simplifies buffor management, while reducing latency response for request-reply operations.